The Complex of Sphingomonas elodea ATCC 31461 Glucose-1-Phosphate Uridylyltransferase with Glucose-1-Phosphate Reveals a Novel Quaternary Structure, Unique among Nucleoside Diphosphate-Sugar Pyrophosphorylase Members - Aragão, David (American Society for Microbiology, 2007)
Gellan gum is a widely used commercial material, available in many different forms. Its economic importance has led to studies into the biosynthesis of exopolysaccharide gellan gum, which is industrially prepared in high yields using Sphingomonas elodea ATCC 31461. Glucose-1-phosphate uridylyltransferase mediates the reversible conversion of glucose-1-phosphate and UTP into UDP-glucose and pyrophosphate, which is a key step in the biosynthetic pathway of gellan gums. Here we present the X-ray crystal structure of the glucose-1-phosphate uridylyltransferase from S. elodea. The S. elodea enzyme shares strong monomeric similarity with glucose-1-phosphate thymidylyltransferase, several structures of which are known, although the quaternary structures of the active enzymes are rather different. A detailed comparison between S. elodea glucose-1-phosphate uridylyltransferase and available thymidylyltransferases is described and shows remarkable structural similarities, despite the low sequence identities between the two divergent groups of proteins.